A polyphenol-rich plant extract prevents hypercholesterolemia and modulates gut microbiota in western diet-fed mice - Langhi, Cédric; Vallier, Marie; Bron, Auriane; Otero, Yolanda F.; Maura, Maheva; Le Joubioux, Florian; Blomberg, Niek; Giera, Martin; Guigas, Bruno; Maugard, Thierry; Chassaing, Benoit; Peltier, Sébastien; et al. (Frontiers in Cardiovascular Medicine, 2024)
Totum-070 is a combination of five plant extracts enriched in polyphenols to target hypercholesterolemia, one of the main risk factors for cardiovascular diseases. The aim of this study was to investigate the effects of Totum-070 on cholesterol levels in an animal model of diet-induced hypercholesterolemia. C57BL/6JOlaHsd male mice were fed a Wwestern diet and received Totum-070, or not, by daily gavage (1g/kg and 3g/kg body weight) for 6 weeks. The Wwestern diet induced obesity, fat accumulation, hepatic steatosis and increased plasma cholesterol compared with the control group. All these metabolic perturbations were alleviated by Totum-070 supplementation in a dose-dependent manner. Lipid excretion in feces was higher in mice supplemented with Totum-070, suggesting inhibition of intestinal lipid absorption. Totum-070 also increased the fecal concentration of short chain fatty acids, demonstrating a direct effect on intestinal microbiota. The characterization of fecal microbiota by 16S amplicon sequencing showed that Totum-070 supplementation modulated the dysbiosis associated with metabolic disorders troubles. Specifically, Totum-070 increased the relative abundance of Muribaculum (a beneficial bacterium bacteria) and reduced that of Lactococcus (a genus positively correlated with increased plasma cholesterol level a deleterious genus). Together, these findings indicate that the cholesterol-lowering effect of Totum-070 bioactive molecules is presumably could be mediated through multiple actions on the intestine and gut microbiota.